Letter from Carl D. Duncan to Patricia Whiting, April 11, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan discusses the nature of his relationship with Whiting and mentions plans to see an opera in Indiana and a play in San Francisco.